Rheological and hydration characterization of calcium sulfoaluminate cement pastes - García-Maté, Marta; Santacruz-Cruz, María Isabel; Gómez-de-la-Torre, María de los Ángeles; León-Reina, Laura; García-Aranda, Miguel Ángel (My University, 2015)
Calcium sulfoaluminate (CSA) cements are currently receiving a lot of attention because their manufacture produces less CO2 than ordinary Portland cement (OPC). However, it is essential to understand all parameters which may affect the hydration processes. This work deals with the study of the effect of several parameters, such as superplasticizer (SP), gypsum contents (10, 20 and 30 wt%) and w/c ratio (0.4 and 0.5), on the properties of CSA pastes during early hydration. This characterization has been performed through rheological studies, Rietveld quantitative phase analysis of measured x-ray diffraction patterns, thermal analysis and mercury porosimetry for pastes, and by compressive strength measurements for mortars. The effect of the used SP on the rheological properties has been established. Its addition makes little difference to the amount of ettringite formed but strongly decreases the large pore fraction in the pastes. Furthermore, the SP role on compressive strength is variable, as it increases the values for mortars containing 30 wt% gypsum but decreases the strengths for mortars containing 10 wt% gypsum.
Keywords: Reología; Cemento; Rheology; Hydration; X-Ray Diffraction; Compressive Strength; Cement Paste; Sulfoaluminate